Disentangling the biogeography of ship biofouling: barnacles in the Northeast Pacific. Issue 6 (21st March 2016) - Ashton, G. V.; Davidson, I. C.; Geller, J.; Ruiz, G. M.
Abstract: Aim: The movement of biofouling organisms by ships results in the transfer of marine species across biogeographical boundaries on a global scale. We used barnacles, a relatively well‐studied taxon, to investigate the extent to which modern commercial vessels disperse biofouling species beyond their current known ranges. Location: Vessels predominantly operated in the North Pacific; sampling was conducted in Los Angeles (CA), Portland (OR), Ketchikan (AK) and Apra Harbor (GU). Methods: Barnacles were collected from submerged surfaces of commercial vessel hulls and identified to the lowest taxonomic unit using a combination of taxonomic and molecular phylogenetic techniques. Their known native and non‐native geographical ranges were assessed and compared with the voyage history of the vessels. Results: Forty distinct taxonomic groups of barnacles (22 assigned to species) were detected from 15 vessels. Six of these recognized species have a world‐wide distribution, due to natural and anthropogenic dispersal. Sixteen species were on vessels with voyage routes that extend beyond the barnacles' known distributions, including 12 species sampled outside of their known range. Main conclusions: A diverse suite of barnacle species is in continuous motion globally on commercial vessel hulls, and the potential scale of this transfer is underscored by the documented species richness for ship biofouling and what is known about the global fleet of vessels. We estimate roughly 680, 000 separate arrival events per year for barnacle species to US ports distributed on both Atlantic and Pacific coasts. Genetic methods revealed high richness compared with previous studies, and the real rate is likely to be much higher than this because (1) it is likely that not all species on a vessel were sampled and (2) only a subset of sampled barnacles were successfully sequenced. Our limited knowledge about the total species pool in flux on ship hulls around the globe constrains our ability to analyse and interpret processes affecting species distribution patterns in the Anthropocene.